MIDDLE ECONOMIC GROWTH TOWARDS TO DEVELOPMENT OF E-COMMERCE IN SOUTHEAST ASIA - Ika Sari Hastuti; Asep Kusdiman Jauhari (JEES: Journal of Economic Empowerment Strategy, 2021)
The rapid development of information and communication technology has resulted in the emergence of a new economy marked by the phenomenon of internet-based business or e-commerce. The economic growth of the middle class of Southeast Asian people in the digital economy era is moving towards a non-cash transaction system and changing the lifestyle of people who depend on the internet for traveling, shopping and doing business online as well as creating new phenomena for the growth of the e-commerce industry or electronic commerce is attractive and growing rapidly. What is interesting is how the influence of middle class economic growth on the development of e-commerce in Southeast Asia. The method used in conducting this research is descriptive qualitative which aims to describe the phenomenon of the growth of the middle class in the development of e-commerce in Southeast Asia systematically for research and problem solving. The estimation results of this study are that with the increasing number of middle class people who use technology for business activities in the network, the development of e-commerce in ASEAN is marked by the use of electronic payment methods or cashless payments where business transaction processes become more efficient and stimulate economic growth. The emergence of new startups. The challenge for the use of e-commerce is readiness in overcoming problems related to ICT such as cyber security, internet networks and adequate ICT infrastructure. Every country in Southeast Asia has advantages and limitations in the use of e-commerce but digital globalization forces countries in Southeast Asia that are experiencing an economic growth to be prepared to build e-commerce infrastructure, especially for MSMEs by utilizing e-commerce to open new markets that are more and the government must prepare infrastructure and regulations that support entrepreneurs to compete in the current e-commerce era.